Use of hydroxychloroquine and chloroquine in COVID-19: How good is the quality of randomized controlled trials? (2020)
Objectives: We critically evaluated the quality of evidence and quality of harms reporting in clincal trials that recently evaluated the effectiveness of HCQ/CQ in COVID-19. Study Design and Setting: Scientific databases were systematically searched to identify relevant trials of HCQ/CQ in COVID-19 published until 10th September, 2020. The Cochrane risk-of-bias tools for randomized trials and non-randomized studies of interventions were used to assess risk of bias of included studies. A 10-item Consolidated Standards of Reporting Trials (CONSORT) harms extension was used to assess for quality of harms reporting. Results: Sixteen trialsincluding fourteen randomized and two non-randomized trials met the inclusion criteria. The results from included trials were conflicting, lacked effect estimates adjusted for confounders and baseline disease severity or comorbidities in many cases, and recruited a fairly small cohort of patients. None of the clinical trials met the CONSORT criteria in full for reporting harms data in clinical trials. None of the sixteen trials had an overall ‘low’ risk of bias, while four of the trials had ‘high’, ‘critical’, and ‘serious’ risk of bias. Biases observed in these trials arise from the randomization process, potential deviation from intended interventions, outcome measurement, selective reporting, confounding, participant selection, and/or classification of interventions Conclusion: In general, the quality of currently available evidence for the effectiveness of CQ/HCQ in COVID-19 is suboptimal. The importance of a properly designed and reported clinical trial cannot be overemphasized amid the COVID-19 pandemic and its dismissal could lead to poorer clinical and policy decisions resulting in wastage of already stretched invaluable healthcare resources.